2018
DOI: 10.31925/farmacia.2018.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profiling, Antioxidant and Cardioprotective Properties of Pinot Noir Cultivar Pomace Extracts

Abstract: Fresh and fermented pomace extracts from Vitis vinifera L. Pinot noir were investigated. Total phenolic index, condensed tannins, total anthocyanins, proanthocyanidins, flavan-3-ol monomers, stilbenes and DPPH (2,2-diphenyl-1-picrylhydrazyl) free radical scavenger ability were measured. The effect of seven days pre-treatment on the isoprenaline-induced infarct-like lesion in rats was assessed by monitoring ECG and serum aspartate and alanine transaminase and creatine kinase. Oxidative stress was assessed by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…All GP extracts had moderate inhibitory effect on MDA formation (p < 0.01). These results may be linked to the finding that flavan-3-ols monomers reduce LDL oxidizability through their incorporation into the LDL particles and the radical trapping effects (Annunziata et al, 2018;Annunziata et al, 2019) and to our previous study which reported an important content of flavan-3-ols monomers in the GP extracts (Balea et al, 2018b;Balea et al, 2018a). There were no significant differences between the effects on MDA of the two grape varieties or between fresh and fermented GP extracts of the same variety (p > 0.05) ( Table 3).…”
Section: In Vivo Antioxidant Effectssupporting
confidence: 52%
See 1 more Smart Citation
“…All GP extracts had moderate inhibitory effect on MDA formation (p < 0.01). These results may be linked to the finding that flavan-3-ols monomers reduce LDL oxidizability through their incorporation into the LDL particles and the radical trapping effects (Annunziata et al, 2018;Annunziata et al, 2019) and to our previous study which reported an important content of flavan-3-ols monomers in the GP extracts (Balea et al, 2018b;Balea et al, 2018a). There were no significant differences between the effects on MDA of the two grape varieties or between fresh and fermented GP extracts of the same variety (p > 0.05) ( Table 3).…”
Section: In Vivo Antioxidant Effectssupporting
confidence: 52%
“…In a previous study we found significant concentrations of resveratrol in the Feteascăneagrăand Pinot noir GP extracts, the fresh GP extracts having a higher concentration (Balea et al, 2018a;Balea et al, 2018b). Several in vitro studies have shown that resveratrol has antitumor, antioxidant, anti-inflammatory, cardioprotective and antiplatelet activity, and glycosylated stilbenes have antifungal and antioxidant effects (Flamini et al, 2013).…”
Section: Polyphenols Analysismentioning
confidence: 91%
“…In this sense, the vegetable products were ground in a coffee grinder (RC-21 Electroarges, Arges, Romania) for 5 min. Then, the powders were screened through a 200 µm sieve (Retsch, Haan, Germany) [19,20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Among the polyphenols identified in the extract were malvidin, delphinidin, rutin, quercetin, catechin, coumaric acid, kaempferol, and trans-cinnamic acid, which could explain the prevention of hypertrophy, inflammation, fibrosis, and cardiomyocyte apoptosis observed upon administration of the extract (Chacar et al, 2018;. In addition, the potential in vivo cardioprotective effect of fresh (high condensed tannins and anthocyanin contents) and fermented (high polyphenolic content) GP extracts from V. vinifera L. Pinot noir cultivar from Romania was demonstrated (Balea et al, 2018). In accordance with other studies, GP polyphenols could promote cardioprotection via different mechanisms.…”
Section: Seedmentioning
confidence: 92%
“…In accordance with other studies, GP polyphenols could promote cardioprotection via different mechanisms. For instance, GP treatment effectively attenuated myocardial infarction in rats by reducing serum oxidative biomarkers, such as malondialdehyde, and increasing the serum total oxidative status and antioxidant reserves (Annapurna et al, 2009;Balea et al, 2018).…”
Section: Seedmentioning
confidence: 99%